Manganese acts centrally to activate reproductive hormone secretion and pubertal development in male rats - Lee, Boyeon (2006)
Manganese (Mn) is an important element for normal growth and reproduction. Because Mn accumulates in the hypothalamus and is capable of stimulating puberty-related hormones in female rats, we assessed whether this metal could cause similar effects in male rats. We have demonstrated that MnCl2, when administered acutely into the third ventricle of the brain, acts dose dependently to stimulate luteinizing hormone (LH) release. Furthermore, there was a dose dependent stimulation in the secretion of LH-releasing hormone (LHRH) from the medial basal hypothalamus in vitro, and administration of an LHRH receptor antagonist in vivo blocks Mn-induced LH release. To assess potential chronic effects of the metal, male pups were supplemented with 10 or 25 mg MnCl2 per kg by gastric gavage from day 15 until days 48 or 55, at which times developmental signs of spermatogenesis were assessed. Results demonstrate that while significant effects were not observed with the 10 mg/kg dose, the animals receiving the 25 mg/kg dose showed increased LH (p < 0.05), FSH (p < 0.01) and testosterone (p < 0.01) levels at 55 days of age. Furthermore, there was a concomitant increase in both daily sperm production (p < 0.05) and efficiency of spermatogenesis (p < 0.05), demonstrating a Mn-induced acceleration in spermatogenesis. Our results suggest Mn is a stimulator of prepubertal LHRH/LH secretion and may facilitate the normal onset of male puberty. These data also suggest that the metal may contribute to male precocious pubertal development should an individual be exposed to low but elevated levels of Mn too early in life.